2018
DOI: 10.1016/j.geoderma.2018.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Does soil erosion rejuvenate the soil phosphorus inventory?

Abstract: Phosphorus (P) is an essential nutrient for life. Deficits in soil P reduce primary production and alter biodiversity. A soil P paradigm based on studies of soils that form on flat topography, where erosion rates are minimal, indicates P is supplied to soil mainly as apatite from the underlying parent material and over time is lost via weathering or transformed into labile and less-bioavailable secondary forms. However, little is systematically known about P transformation and bioavailability on sloping and er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 84 publications
(166 reference statements)
0
8
0
Order By: Relevance
“…Landslides are the most likely cause of differences in soil P among eroding hillslope soils (e.g. Peltzer et al, ; Eger et al, ). Mountain beech has well‐developed ectomycorrhizae that enhance uptake of P and other nutrients from infertile soils using a dense fine root network (Wardle, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landslides are the most likely cause of differences in soil P among eroding hillslope soils (e.g. Peltzer et al, ; Eger et al, ). Mountain beech has well‐developed ectomycorrhizae that enhance uptake of P and other nutrients from infertile soils using a dense fine root network (Wardle, ).…”
Section: Discussionmentioning
confidence: 99%
“…Landslides alter soils through physical losses, gains and mixing as well as through chemical changes (Cheng, Yang, Yu, Li, & Zhang, ; Lin et al, ). Chemical weathering of minerals in freshly exposed rocks, particularly of apatite, can lead to greater concentrations of available phosphorus (P) in young soils (Eger et al, ; Peltzer et al, ). With time P is leached from soils or occluded into unavailable forms during soil development (Peltzer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Maintained or increased labile and moderately labile P at Matlock at the 30-60 cm depths in the BO harvest treatment might be attributed to the direct effect of debris on the amount of P removed during harvest, its indirect influence on belowground decomposition (Devine and Harrington, 2007;Sanchez et al, 2006), or the rate at which plants access P and translocate it to surface soils (Eger et al, 2018). The response may also be associated with the aforementioned Scotch broom effect because the BO treatment had a markedly lower amount of Scotch broom present at the Matlock site (Harrington and Schoenholtz, 2010;D.…”
Section: Discussionmentioning
confidence: 99%
“…Vystavna et al (2017) reported a long-term variation of total phosphorus concentrations measured over 53 years in the Slapy Reservoir, Czechia, which ranged 10 to 118 µg/L. Soil erosion is considered a main contributor (especially during floods) of phosphorus to streams, lakes, or other water bodies (Eger et al, 2018). However, agricultural activities, organic wastes in sewage, industrial discharges, cattle manure, construction sites, and urban areas can also contribute phosphorus (Reid et al, 2018).…”
Section: Discussionmentioning
confidence: 99%